Improving Pantun Writing Skills Using the Discovery Learning Model - Wattimena, Stevany; Solissa, Everhard Markiano; Sapulette, Viona (Universitas Pattimura, 2023)
The aim of this research is to improve abilities writing rhymes using the Discoveri Learning model for class VII-I students at SMP Kristen 1 West Leihitu. This research design uses classroom action research (PTK). Classroom action research is an examination of activities that are deliberately created and occur in a class. The learning model used in this research uses the Discovery Learning model. This research data was carried out in two cycles. Each cycle consists of four stages, namely the planning stage, action implementation, observation stage, and reflection stage. Form the results of data analysis carried out on students in class VII-I of SMP Kristen 1 West Leihitu, using the discovery learning model can improve their ability to write rhymes. This can be seen from the increase in test results each cycle. The average score for the ability to write rhymes in the cycle is 65, after implementing the discovery learning model. It turned out that the implementation of the cycle II showed an increase in students ability to write pantun with an average score of 78, because the learning outcomes had met the criteria, namely 85.5%, so the research took place in two cycles.